2020
DOI: 10.1002/jpen.1790
|View full text |Cite
|
Sign up to set email alerts
|

New Predictive Equations for Estimating Resting Energy Expenditure in Adults With Crohn's Disease

Abstract: Background Increased resting energy expenditure (REE) has been hypothesized to be a potential cause of weight loss in individuals with Crohn's disease (CD). This study aimed to develop and validate new predictive equations for estimating REE in adults with CD. Methods Adults, ages 18–65 years, with CD were recruited. Anthropometry, indirect calorimetry, and bioimpedance analysis were performed in all patients. Disease activity was assessed by Crohn's Disease Activity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…There are no data on the relationship between PhA and RMR in lung cancer patients. Interestingly, PhA has been found to be a significant predictor of resting energy expenditure in athletes [ 36 ], healthy subjects [ 37 , 38 ], and patients with Crohn’s disease [ 39 ], possibly reflecting the association of PhA with lean mass and muscle quality [ 40 ]. This discrepancy may be due to the inherent differences in the studied populations since we included only male subjects with advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data on the relationship between PhA and RMR in lung cancer patients. Interestingly, PhA has been found to be a significant predictor of resting energy expenditure in athletes [ 36 ], healthy subjects [ 37 , 38 ], and patients with Crohn’s disease [ 39 ], possibly reflecting the association of PhA with lean mass and muscle quality [ 40 ]. This discrepancy may be due to the inherent differences in the studied populations since we included only male subjects with advanced-stage NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, raw BIA variables such as bioimpedance index (BI-Index) and phase angle (PhA) might be taken into account. Given that BI-index is a direct proxy marker of FFM, while PhA is related to body cell mass [17], a relationship between energy expenditure and BI-index and PhA has already been observed in normal-weight or overweight subjects [18] as well as in patients with obesity [19] and Crohn's disease [20].…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the results of these studies showed that the raw BIA variables may improve the prediction power under physiological conditions [18], but only by a limited extent in subjects possibly with altered body water distribution [19,20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the ratio between extracellular water-ECW and total body water-TBW) [ 22 ], body cell mass and cellular integrity [ 23 ]. So far, a relationship between REE and BI-index and/or PhA has already been observed in normal-weight or overweight subjects [ 24 ] as well as in patients with obesity [ 25 ] and Crohn’s disease [ 26 ]. Not surprisingly, the results of these studies suggest that raw BIA variables may improve the prediction power under physiological conditions [ 24 ], but only to a limited extent in subjects with altered body water distribution [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%